Lifestyle Change Improves Individual Health and Lowers Healthcare Costs - Koyama, W. (Methods of Information in Medicine, 2000)
In 1996 the Japanese Ministry of Health and Welfare discontinued the use of the term “Adult onset diseases” used for almost 40 years, and replaced it by “Lifestyle-related diseases”; a meaningful change.Lifestyle is one of the greatest problems facing Japan today. Considering the rapid aging of Japanese society and the continuing increase in medical costs, it is important for all citizens to be concerned not only about their own health but also about the impact on the financial health of the nation as a whole.Our data indicate that the greatest determining factor for increased health-care costs is the percentage of patients hospitalized, and the variable with the greatest influence on this is the relative number of hospital beds available. On the other hand, the variable with the greatest inhibitory effect on the growth of healthcare costs is the availability of guidance to improve lifestyle factors.
Keywords: High Ratio of the Elderly; Lifestyle-related Diseases; Healthcare Costs